2019
DOI: 10.21776/ub.jam.2019.017.01.19
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Turnover Intention by Employee Development in Garment Companies

Abstract: The aim of this study is to determine the role of employee development carried out by garment companies to minimize the emergence of turnover intention among garment workers in Indonesia. This study using survey data conducted by the collaborations between the University of Indonesia (UI), Tufts University (TU), Better Work-ILO (BW) and Real-TimeAnalytics (RTA) Vietnam, which is collected from 109 garment companies and 2580 respondents in the garment sector. The data were analyzed using structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This results are in line with previous study conducted by Ref. [ 4 ] on garment factory workers in Indonesia. In this study, the more knowledge and skills obtained by employees through training, and the more challenges employees face during the promotion, the more effort they make to be more effective at their jobs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This results are in line with previous study conducted by Ref. [ 4 ] on garment factory workers in Indonesia. In this study, the more knowledge and skills obtained by employees through training, and the more challenges employees face during the promotion, the more effort they make to be more effective at their jobs.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Ref. [ 4 ] study found that the growth mind-set possessed by employees increased empowerment carried out by the company to reduce the turnover intention rate. Discussion on those important variable can be explained as beneath.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Research confirms that opportunities to apply learned skills lead to further development and growth (Oosthuizen et al ., 2019; Rigby and Ryan, 2018). However, these scholars deplored the fact that although growth opportunities are critical for women to advance in their careers, fewer women than men are given such opportunities within organizations (Kurniawati and Sari, 2019; Lewis and Beauregard, 2018; Moalusi and Jones, 2019). Growth opportunities are vital for women to progress, especially when these opportunities are aligned with the requirements for specific senior roles.…”
Section: Discussionmentioning
confidence: 99%
“…Women participants commented that prioritizing women is a practice that supports their career progression. Prior research acknowledged the need to prioritize women to see them Organiza onal impediments towards women's career advancement Women's career advancement advance in the workplace (Kurniawati and Sari, 2019;McKinsey and Company, 2019). This practice implies treating gender matters as a priority and putting women at the forefront of these tactics.…”
Section: Organizational Practices Necessary For Women Career Advancementmentioning
confidence: 99%
See 1 more Smart Citation